Phenotypic characterisation of pro-inflammatory monocytes and dendritic cells in peripheral arterial disease - Dopheide, Jörn F.; Obst, Viviane; Doppler, Christopher; Radmacher, Marie-Christine; Scheer, Martin; Radsak, Markus P.; Gori, Tommaso; Warnholtz, Ascan; Fottner, Christian; Daiber, Andreas; Münzel, Thomas; Espinola-Klein, Christine (Thrombosis and Haemostasis, 2012)
Atherosclerosis is a chronic inflammatory process involving antigen-presenting cells like monocytes and dendritic cells (DC). The aim of this study was to perform a phenotypic characterisation of these cell types in patients with different degrees of peripheral arterial disease (PAD). Sixty patients with PAD [N= 30 intermittent claudication (IC), N= 30 critical limb ischemia (CLI)] and 30 controls were included. Peripheral blood leucocytes were analysed from peripheral blood by flow cytometry using different gating strategies to directly identify and analyse monocytes, myeloid DC, (mDC) and plasmacytoid DC (pDC). PAD patients showed a significantly higher proportion of proinflammatory CD14++CD16+ monocytes (p<0.0001) compared with healthy individuals. We found an increased number of mDC/ml and a reduced number of pDC/ml (both p<0.01) in PAD patients, leading to a shift in the mDC/pDC ratio (p<0.01). As compared to patients with intermittent claudication, CLI patients presented a reduced expression of HLA-DR (p<0.01), CD86 and CD40 on both mDCs and pDCs (p<0.01). Peripheral blood monocytes show a proinflammatory phenotype in PAD patients compared to controls. In contrast, CLI patients show a reduced expression of proinflammatory markers. We hypothesise that severe ischaemia and/or prolonged inflammation in CLI might lead to a paradoxical attenuation in the proinflammatory membrane pattern of circulating mononuclear cells, possibly hindering an adequate regulatory function of mDCs and pDCs and favouring the progression of disease.
Keywords: Monocytes; dendritic cells; inflammation; peripheral arterial disease